Proinflammatory activation of microglia in the cerebellum hyperexcites Purkinje cells to trigger ataxia. (May 2023) - Xie, Shu-Tao; Fan, Wen-Chu; Zhao, Xian-Sen; Ma, Xiao-Yang; Li, Ze-Lin; Zhao, Yan-Ran; Yang, Fa; Shi, Ying; Rong, Hui; Cui, Zhi-San; Chen, Jun-Yi; Li, Hong-Zhao; et al.
Abstract: Specific medications to combat cerebellar ataxias, a group of debilitating movement disorders characterized by difficulty with walking, balance and coordination, are still lacking. Notably, cerebellar microglial activation appears to be a common feature in different types of ataxic patients and rodent models. However, direct evidence that cerebellar microglial activation in vivo is sufficient to induce ataxia is still lacking. Here, by employing chemogenetic approaches to manipulate cerebellar microglia selectively and directly, we found that specific chemogenetic activation of microglia in the cerebellar vermis directly leads to ataxia symptoms in wild-type mice and aggravated ataxic motor deficits in 3-acetylpyridine (3-AP) mice, a classic mouse model of cerebellar ataxia. Mechanistically, cerebellar microglial proinflammatory activation induced by either chemogenetic M3D(Gq) stimulation or 3-AP modeling hyperexcites Purkinje cells (PCs), which consequently triggers ataxia. Blockade of microglia-derived TNF-α, one of the most important proinflammatory cytokines, attenuates the hyperactivity of PCs driven by microglia. Moreover, chemogenetic inhibition of cerebellar microglial activation or suppression of cerebellar microglial activation by PLX3397 and minocycline reduces the production of proinflammatory cytokines, including TNF-α, to effectively restore the overactivation of PCs and alleviate motor deficits in 3-AP mice. These results suggest that cerebellar microglial activation may aggravate the neuroinflammatory response and subsequently induce dysfunction of PCs, which in turn triggers ataxic motor deficits. Our findings thus reveal a causal relationship between proinflammatory activation of cerebellar microglia and ataxic motor symptoms, which may offer novel evidence for therapeutic intervention for cerebellar ataxias by targeting microglia and microglia-derived inflammatory mediators. Graphical Abstract: ga1